Induced Production, Synthesis, and Immunomodulatory Action of Clostrisulfone, a Diarylsulfone from Clostridium acetobutylicum. Issue 68 (3rd November 2020) - Neuwirth, Toni; Letzel, Anne‐Catrin; Tank, Cedric; Ishida, Keishi; Cyrulies, Michael; Schmölz, Lisa; Lorkowski, Stefan; Hertweck, Christian
Abstract: The anaerobe Clostridium acetobutylicum belongs to the most important industrially used bacteria. Whereas genome mining points to a high potential for secondary metabolism in C. acetobutylicum, the functions of most biosynthetic gene clusters are cryptic. We report that the addition of supra‐physiological concentrations of cysteine triggered the formation of a novel natural product, clostrisulfone (1 ). Its structure was fully elucidated by NMR, MS and the chemical synthesis of a reference compound. Clostrisulfone is the first reported natural product with a diphenylsulfone scaffold. A biomimetic synthesis suggests that pentamethylchromanol‐derived radicals capture sulfur dioxide to form 1 . In a cell‐based assay using murine macrophages a biphasic and dose‐dependent regulation of the LPS‐induced release of nitric oxide was observed in the presence of 1 . Abstract : Induction of the industrial anaerobe Clostridium acetobutylicum with cysteine led to the discovery of an unprecedented diarylsulfone natural product named clostrisulfone that likely results from sulfur dioxide capture by chromane‐derived radicals. Its structure was elucidated by NMR and confirmed by synthesis. The tocopherol‐related molecule exerts immunomodulatory activities (see figure).